(untitled) (Estudios Gerenciales, 2014)
Whendeciding in which segment to invest orhowto distribute the marketing budget, managers generallytake risks in making decisions without considering the real impact every client or segment has over organizationalprofits. In this paper, a segmentation framework is proposed that considers, firstly, the calculationof customer lifetime value, the current value, and client loyalty, and then the building of client segmentsby self-organized maps. The effectiveness of the proposed method is demonstrated with an empiricalstudy in a cane sugar mill where a total of 9 segments of interest were identified for decision making.